Hydrological study and estimating flow rate of Sungai Lebir, Kuala Krai, Kelantan - Shravanya, Simmadoraiappanna (2016)
Flood is a common natural disaster that exists in almost every part of the world. One of the most affected town in the year 2014 is Manek Urai. Manek Urai is a small town located about 25 kilometres from Kuala Krai town in Kelantan state. The downpour lasted over 48 hours with continues heavy rainfall during the monsoon period. In just a short time, Sungai Galas overflowed and submerged the old town of Gua Musang and the surrounding villages including Manek Urai through Sungai Lebir. The scenario became even worst from year to year. In this research, the catchment area of Sungai Lebir is selected. Thus, this study was carried out to estimate the flow rate of Sungai Lebir and analyse the rainfall data using seven selected hydrology stations in Sungai Lebir catchment. Flood is difficult to avoid. Hence, it is appropriate to carry out forecasting and take precaution in future. HEC-HMS was used in order to estimate the flow rate by analysing rainfall data which acquired from Department of Irrigation Drainage (DID). By creating the river model based on the actual data and satellite image, the true phenomenon of what is really happened can be understood